The emergency department services on the monitoring of direct oral anticoagulants - Alshammari, Munifah Afit; Altayawi, Fahad Mohammed; Alonezi, Abdulelah Dawas; Kabi, Abdullah Hashem; Almutairi, Adel Zayed; Albahouth, Ahmed Abdulaziz A; Almutairi, Fahad Ghazi; Alanazi, Maha Mahdi; Alaoufi, Sami Mohammed; Alotaibi, Hamad Marshud; Alanazi, Anood Fahad; Baurasien, Bander Khalid (International journal of health sciences, 2020)
Background: Direct oral anticoagulants (DOACs) such as dabigatran, rivaroxaban, apixaban, and edoxaban are increasingly used due to their benefits over warfarin, including reduced risk of intracranial hemorrhage and fewer dietary and drug interactions. Despite these advantages, the management of DOACs involves complexities like dose adjustments for renal or hepatic impairment, potential drug-drug interactions, and high costs, leading to prevalent off-label use. Aim: This study aims to evaluate the effect of Anticoagulation management services (AMS) on the management of DOAC therapy compared to non-AMS management, focusing on healthcare utilization and anticoagulation-related outcomes in the emergency department. Methods: A retrospective cohort analysis was conducted at the University of Utah Health, analyzing data from adult patients prescribed DOACs. Patients were categorized into AMS and non-AMS groups based on management approach. The study assessed the frequency and types of encounters, interventions related to DOAC therapy, and clinical outcomes such as thromboembolic events, bleeding, and mortality. Results: Patients managed by AMS had more frequent interactions regarding DOAC therapy but did not show significant improvement in clinical outcomes compared to non-AMS managed patients. The AMS group had slightly higher bleeding events, which might be attributed to higher comorbidity scores and poorer renal function.